2013
DOI: 10.5812/hepatmon.7415
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Viral Load of HBV in Chronic Hepatitis B Patients and Precore and Basal Core Promoter Mutations

Abstract: BackgroundMore than two billion people have been exposed to hepatitis B virus (HBV) worldwide. Furthermore, four hundred million of them are infected with chronic HBV infection. The predominant mutation of the precore region involves a G to A change at nucleotide1896, which creates a premature stop codon at codon 28. Two mutations of A1762T and G1764A are reported as the most prevalent mutations in the basal core promoter (BCP).ObjectivesThe purpose of this study was to investigate the relationship between mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…www.ajpp.in In present study we observed that the HBV DNA load was high in HBeAg positive cases, and good correlation was seen between the two, but in 26% of HBeAg negative cases the HBV DNA levels were > 20,000 IU/mL which is the level at which treatment is started, monitoring these patients only on basis of HBeAg can be misleading in such cases. Such findings are generally observed in patients with precore mutations (Ghabeshi et al, 2013). Moreover 46 (62.16%) HBeAg negative patients had HBV DNA level more than 29 IU/mL.…”
Section: Resultsmentioning
confidence: 61%
“…www.ajpp.in In present study we observed that the HBV DNA load was high in HBeAg positive cases, and good correlation was seen between the two, but in 26% of HBeAg negative cases the HBV DNA levels were > 20,000 IU/mL which is the level at which treatment is started, monitoring these patients only on basis of HBeAg can be misleading in such cases. Such findings are generally observed in patients with precore mutations (Ghabeshi et al, 2013). Moreover 46 (62.16%) HBeAg negative patients had HBV DNA level more than 29 IU/mL.…”
Section: Resultsmentioning
confidence: 61%
“…The low HBV viral load in our series could explain this- in fact, recent data suggest a significant relationship between high HBV viral load and frequency of PC/BCP mutations in chronic hepatitis B [47]. We tested a small number of patients and this precludes more definitive conclusions.…”
Section: Discussionmentioning
confidence: 66%
“…Genotype C is prevalent in Asia and the Pacific. Genotype D shows frequently precore mutations and is prevalent in the Mediterranean region and Southern Europe ( 11 ). In patients with HCC in Romania, we detected both core and precore mutations in tissue samples.…”
Section: Discussionmentioning
confidence: 99%